2020
DOI: 10.1007/s10142-020-00736-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis EA-CB0575 genome reveals clues for plant growth promotion and potential for sustainable agriculture

Abstract: El crecimiento demográfico proyectado a corto y mediano plazo exige pensar estrategias oportunas que permitan la ejecución de prácticas agrícolas amigables con el medio ambiente Una reciente investigación de la U usó una rizobacteria (Bacillus subtilis EA-CB0575), extraída de cultivos de banano del Urabá antioqueño para determinar su efecto en el crecimiento de la planta del tomate Chonto-Santa Cruz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 73 publications
8
36
0
2
Order By: Relevance
“…ED5 strain demonstrated strong siderophore activity and siderophore enterobactin (fes, entFS, and fepA) biosynthesis pathway was also observed in its genome study. Consistent with this study, the siderophore enterobactin pathway (fepEGDC) was detected in E. cloacae SBP-8 (Singh et al, 2017) and Bacillus subtilis EA-CB0575 genomes (Franco-Sierra et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…ED5 strain demonstrated strong siderophore activity and siderophore enterobactin (fes, entFS, and fepA) biosynthesis pathway was also observed in its genome study. Consistent with this study, the siderophore enterobactin pathway (fepEGDC) was detected in E. cloacae SBP-8 (Singh et al, 2017) and Bacillus subtilis EA-CB0575 genomes (Franco-Sierra et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Systems biology can annotate the gene function of B. subtilis through omics analysis. Metabolomics analysis of B. subtilis EA-CB0575 revealed that some genes can promote plant growth [ 63 ]. Through genetic manipulation of these genes, agriculture will be greatly developed.…”
Section: Systematic Biology Advances In B Subtilismentioning
confidence: 99%
“…Siderophores are low molecular weight compounds (500-1,500 Da) possessing a high affinity for Fe 3+ (K f > 10 30 ) (Haas & Defago, 2005) and they are synthesized by bacteria through non-ribosomal pathways (Hutchins et al, 1999;Khan et al, 2020). Many PGPB have been reported to produce siderophores, such as Bacillus subtilis, Paenibacillus polymyxa SK1, Mesorhizobium sp., Brevibacillus brevis GZDF3 (Franco-Sierra et al, 2020;Khan et al, 2020;Menéndez et al, 2020;Sheng et al, 2020). The chelate of siderophores and ferric iron can be directly absorbed by plants and are called mechanism III, which is thought to be used by plants to resist iron stress (Shenker et al, 1992;Yehuda et al, 1996;Chen, Dick & Streeter, 2000).…”
Section: Introductionmentioning
confidence: 99%